2012
DOI: 10.1155/2012/275624
|View full text |Cite
|
Sign up to set email alerts
|

African American Race and Prevalence of Atrial Fibrillation:A Meta-Analysis

Abstract: Background. It has been observed that African American race is associated with a lower prevalence of atrial fibrillation (AF) compared to Caucasian race. To better quantify the association between African American race and AF, we performed a meta-analysis of published studies among different patient populations which reported the presence of AF by race. Methods. A literature search was conducted using electronic databases between January 1999 and January 2011. The search was limited to published studies in Eng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…A meta‐analysis of 10 studies examining the prevalence of AF among African‐Americans in the USA compared with Whites, concluded that being African‐American was associated with a “protective effect” from AF (OR 0.51, 95% CI 0.44‐0.59, P < .001). Despite the lower prevalence of AF, African‐Americans in the USA have twice the risk of first ever stroke compared with Whites …”
Section: Ethnicity Age and Prevalence Of Afmentioning
confidence: 93%
“…A meta‐analysis of 10 studies examining the prevalence of AF among African‐Americans in the USA compared with Whites, concluded that being African‐American was associated with a “protective effect” from AF (OR 0.51, 95% CI 0.44‐0.59, P < .001). Despite the lower prevalence of AF, African‐Americans in the USA have twice the risk of first ever stroke compared with Whites …”
Section: Ethnicity Age and Prevalence Of Afmentioning
confidence: 93%
“…[43] The authors found that the overall prevalence of AF was higher in men than in women for all age groups, but because there were almost twice the number of women than men >75 years in the general population, the absolute numbers of women and men with AF were similar. A recent meta-analysis[44] of 10 studies involving 1,031,351 subjects found a markedly lower prevalence of AF in African Americans compared to Caucasians (OR 0.51, 95%CI 0.44 – 0.59, P<0.001) in both the general population and in those over 60 years of age.…”
Section: Tachyarrhythmiasmentioning
confidence: 99%
“…Atrial fibrillation is not common in African populations, either native on the continent or in the America [19]. There must be a genetic angle to it as African Americans are less encumbered than white Americans [20]. The low prevalence of established risks already alluded to here may be why African rural populations [21] have a strikingly low rate of atrial fibrillation than urban African and western populations.…”
Section: Discussionmentioning
confidence: 90%